2010
DOI: 10.1111/j.1398-9995.2010.02448.x
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal tissue polyclonal IgE is functional in response to allergen and SEB

Abstract: We here demonstrate that mucosal IgE abs in NP tissue are functional and able to activate mast cells; specific IgE abs in NP tissue can be found independently of their presence in serum. We postulate that superantigen-induced polyclonal IgE in airway disease contributes to chronic inflammation by continuously activating mast cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
154
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(165 citation statements)
references
References 19 publications
8
154
1
2
Order By: Relevance
“…Interestingly, this polyclonal IgE from mucosal tissue appears to be functional, and may induce mast cell degranulation to numerous inhalant allergens. Together with the fact that SEB may serve as an allergen, these findings may contribute to persistent inflammation by continuously activating mast cells [60]. These findings confirm the role played by S. aureus enterotoxins as disease modifiers in CRSwNP [61,62].…”
Section: Role Of Staphylococcal Enterotoxins In Airway Diseasesupporting
confidence: 69%
“…Interestingly, this polyclonal IgE from mucosal tissue appears to be functional, and may induce mast cell degranulation to numerous inhalant allergens. Together with the fact that SEB may serve as an allergen, these findings may contribute to persistent inflammation by continuously activating mast cells [60]. These findings confirm the role played by S. aureus enterotoxins as disease modifiers in CRSwNP [61,62].…”
Section: Role Of Staphylococcal Enterotoxins In Airway Diseasesupporting
confidence: 69%
“…The locally formed IgE is polyclonal, with IgE antibodies against several hundred or more allergens, and functional, even in the absence of systemic IgE antibodies or a positive skin-prick test. 916,917 Among those IgE specificities, only staphylococcal enterotoxins have superantigenic activity. CRSwNP showed a significantly higher S. aureus culture-positivity and a higher detection rate of S. aureus superantigens and of specific SE-IgE in a recent meta-analysis.…”
Section: Viiib Crswnp: Comorbid Asthmamentioning
confidence: 99%
“…Staphylococcal superantigens (SAg) have recently been implicated in the pathogenesis of various allergic conditions, e.g. atopic dermatitis, urticaria, allergic rhinitis, nasal polyposis and bronchial asthma [5,6,7,8]. Previous studies have reported that the prevalence of serum-specific immunoglobulin E (IgE) to SAg is related to the severity of asthma and eosinophilic inflammation in adult asthma [9,10,11].…”
Section: Introductionmentioning
confidence: 99%